Mechanism of Goods and Services Procurement Implementation from the Perspective of Legal Certainty in Natuna Police Station - Darwinsyah, ‎; Suwondo, Denny (KnE Social Sciences, 2025)
The procurement of government goods and services is an integral part of state financial management, which must be carried out in a transparent, efficient, and accountable manner to support the performance of public services. In the context of law enforcement agencies, such as the National Police, procurement plays an important role in supporting institutional operations, especially in strategic areas such as the Natuna Police in border areas. However, in practice, procurement implementation often faces various administrative, technical, and structural obstacles that have implications for legal certainty. This research aims to analyze the mechanism for implementing the procurement of goods and services at the Natuna Police Station from the perspective of legal certainty, as well as identify inhibiting factors and efforts to strengthen them. This study uses an empirical juridical approach using a qualitative method. The approach used includes a statute approach to analyze applicable regulations, a case approach to procurement practices at the Natuna Police Station, and a conceptual approach to understanding relevant legal principles. Data were obtained through interviews, observations, and the study of documents and regulations related to the implementation of procurement. The theories used as knives for analysis are Sudikno Mertokusumo’s Legal Certainty Theory and Lawrence M. Friedman’s Legal System Theory. The results show that although the Natuna Police has referred to Presidential Regulation No. 16/2018 and internal police regulations, there are still structural constraints, unsynchronized regulatory substances, and a weak culture of legal compliance. Therefore, strengthening the supervisory system, digitizing procurement, and increasing the capacity of human resources are important steps in ensuring legal certainty in the implementation of procurement.